Inventory systems : modeling and research methods - Wee, Hui-Ming (Management science--theory and applications series., 2011)
"Most organizations use, transform, distribute or sell materials of one or several kinds. The management of materials has serious implication on the financial, production, and marketing functions of an organization. As the level of complexity of a product increases, so does the importance of managing materials. To fulfill their role in providing products and services, enterprises must satisfy the needs of production, as well as services through the use of all resources such as labor, capital, equipment and materials. All these managerial activities are called materials management"--Publisher's website.